2016
DOI: 10.18632/oncotarget.12691
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CK19 is an independent predictor of negative outcome for patients with squamous cell carcinoma of the tongue

Abstract: ObjectivesTo explore the prognostic role of CK19 expression in squamous cell carcinomas within a well-defined cohort of oral tongue cancer patients.MethodsIn our retrospective study, we investigated 129 patients with tongue cancer that had suitable material for inclusion in a tissue microarray (TMA). Where possible, samples were taken from central and peripheral regions of the tumor to generate a representative sample of the tumor. The expression level of CK19 was assessed by immunohistochemical staining.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, in head and neck cancer, new cut-off levels of 131 and 300 copies/μl were proposed by different studies [9, 36]. Head and neck tumours are squamous cell carcinomas and expression of KRT19 is a poor prognostic marker [37]. Most breast, gastric, colorectal, and between the 40 and 60% of lung malignancies, are adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…However, in head and neck cancer, new cut-off levels of 131 and 300 copies/μl were proposed by different studies [9, 36]. Head and neck tumours are squamous cell carcinomas and expression of KRT19 is a poor prognostic marker [37]. Most breast, gastric, colorectal, and between the 40 and 60% of lung malignancies, are adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…CK19 is mainly expressed in the basal cells of the normal oral squamous epithelium, but it is upregulated and abnormally distributed in OSCC. Therefore, CK19 overexpression is an early event in oral mucosa carcinogenesis and its abnormal expression is used as one of the reliable biomarkers in the early diagnosis of OSCC 49‐51 . Furthermore, some studies reported that the loss of cytokeratin 13 expression and cytokeratin 17 overexpression may be useful in distinguishing oral precancerous lesions from reactive oral lesions with atypical epithelium, suggesting that both CK13 and CK17 may play an important role in the progression of OSCC 52‐54 (Figure 1).…”
Section: Alteration Of the Cytoskeletonmentioning
confidence: 99%
“…Aside from being employed as a diagnostic biomarker, CKs are also found to harbour potential prognostic value in various epithelial cell-associated carcinomas [ 48 50 ]. Importantly, numerous studies have shown the significant correlation between CKs (especially 8, 18 and 19) and poor prognosis of HNSCC [ 50 , 51 ], warranting further investigation. In summary, we have reported significantly elevated expression levels of CK 8 and 18 in saliva collected from HPV-negative patients, with simultaneously elevated expression levels of CK 17, 18 and 19 in saliva collected from HPV-positive HNSCC patients.…”
Section: Discussionmentioning
confidence: 99%